Regularities of free radical processes and involutional changes of face and neck skin in different age groups - Silina EV; Stupin VA; Bolevich SB; Manturova NE (Dove Medical Press, 2018)
EV Silina,1 VA Stupin,2,3 SB Bolevich,1 NE Manturova2,4 1Department of Human Pathology, I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russia; 2Institute of Plastic Surgery and Cosmetology, Moscow, Russia; 3Department of Hospital Surgery №1, Pirogov Russian National Research Medical University (RNRMU), Moscow, Russia; 4Department of Plastic and Reconstructive Surgery, Cosmetology and Cell Technologies, Pirogov Russian National Research Medical University (RNRMU), Moscow, Russia Aim: The purpose of this study was to examine the role of free radical oxygen and peroxide–lipid processes along with conducting the study of blood flow level and oxygen saturation of facial tissues in patients of different ages with varying degrees of involutional changes in the skin of the face and neck.Materials and methods: One hundred and fifty-three people (84.3% women and 15.7% men) aged from 26 to 78 years with varying degrees of involutional changes in facial skin were examined. The clinical and laboratory evaluation was carried out dynamically and included various indicators of free radical processes, objective and subjective clinical visualization, and laser Doppler flowmetry (LDF) of the facial skin and transcutaneous oximetry (TcpO2) performed at 10 points on the face. To assess the state of free radical processes, the authors investigated the basal indicator of chemiluminescence intensity (ICb), the intensity of chemiluminescence stimulated (ICs) by zymosan, the activity coefficient (AC) of chemiluminescence, antiperoxide activity of plasma, and malondialdehyde (MDA).Results: With aging, the imbalance of the oxygen constituents of free radical processes grows with the increase in ROS. Proportional to age, the ICs increased 2.1 times on average in people older than 55 years compared to that in people younger than 30 years and ICb decreased by 1.8 times. As a result, the AC increased by 5.6 times. This correlates with involuntary skin changes and with regression of microcirculation and TcpO2. According to LDF, it was established that average total blood flow in people younger than 30 years and people older than 55 years was 8.1 and 6.4 mL/min, respectively The difference between the indicators of TcpO2 in people younger than 30 years and people older than 55 years was 1.6 times (average 56 vs 35 mm Hg). The stability of the indicators of the peroxide–lipid link of oxidative stress in different age groups demonstrated that the activation of ROS formation in mitochondria is not a cause but a consequence of microcirculation and metabolic processes in the face and neck and aging in general.Conclusion: The tissue metabolism and microcirculation parameters naturally regress with aging, which is associated with the increase of ROS. The excess of species leads to the intensification of peroxide processes. This, in turn, is reflected in the aesthetic appearance manifested by aging. Keywords: free radical processes, ROS aging, skin, involution processes, microcirculation